PELAKSANAAN INOVASI PELITA SEBAGAI UPAYA PERCEPATAN CAKUPAN DOKUMEN AKTA KEMATIAN DI KABUPATEN SRAGEN - Ardyati, Rizda; Tristiana, Enis; Yulianti, Sri Wahyuningsih (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2024)
The Sragen Regency Population and Civil Registration Service has published an innovation related to recording Death Certificates, namely the Pelita Innovation or Direct Reporting of Death Issued Deed. Pelita's innovation is in collaboration with local villages/sub-districts. The service was carried out with the aim of introducing the presence of Pelita innovation, because the Death Certificate recording service in its implementation was still found to be lacking. Because the coverage of Death Certificates is still low. Plumbungan Village, Karangmalang District, Sragen Regency. As a partner in this community service activity, there are problems, namely the lack of literacy in the target partner community regarding the Pelita Innovation issued by the Population and Civil Registration Service of Sragen Regency and the target partner community's low level of understanding regarding procedures for administering Death Certificates through Pelita Innovation. The activity was carried out in several stages, namely: 1) Preparation Stage, at this stage the service team made preparations, namely discussing and reviewing the problems that dominated the implementation of the Pelita Innovation issued by the Sragen Regency Population and Civil Registration Service. 2) Technical Stage, implementation of workshops related to the socialization of Pelita innovation. 3) Cumulative Stage, namely working together with the community to provide direction regarding Pelita innovation which aims to make it easier for the community to manage Death Certificate documents. As well as disseminating information through distributing leaflets and video appearances. Later, leaflets and videos will also be distributed to the community throughout Plumbungan Village, Karangmalang District, Sragen Regency so that all people can know about the Pelita Innovation issued by the Sragen Regency Population and Civil Registration Service